LEGAL PROTECTION FOR VICTIMS OF NARCOTIC ABUSE IN BAITU SYIFA REHABILITATION INSTITUTION, MEDAN THROUGH A WORSHIP APPROACH - Hari Suyandi R; Zulkarnain Zulkarnain; Ramadhan Syahmedi Siregar (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2020)
The existence of a rehabilitation centre for addicts and victims of narcotics abuse is considered an effective formula to protect the law. In contrast, currently, prisons are considered inappropriate and safe for narcotics addicts to undergo healing. This study examines the worship approach used in the rehabilitation process and the application of legal protection for someone involved in narcotics abuse at the Baitu Syifa Rehabilitation Center from the perspective of the Narcotics Law Number 35 of 2009. This qualitative research uses statutory, case and conceptual approaches. The study results found that the rehabilitation program at Baitu Syifa did not conflict with the provisions in Article 57 of the Law. Number 35 of 2009 states that residents' recovery can be carried out through a religious approach. The recovery of victims of narcotics abuse in Baitu Syifa is in the form of routine activities with Islamic nuances based on the Al-Quran and As-sunnah, which include Islamic Treatment Community (TC), Scientific Islamic Studies, pious practices such as performing obligatory prayers, sunnah services, the Nabawi treating and reading the Koran. The development of worship approach methods at the Baitu Syifa Rehabilitation Center has been adapted to Islamic law.Keberadaan panti rehabilitasi bagi pecandu dan korban penyalahgunaan narkotika dianggap sebagai formula jitu sebagai upaya perlindungan hukum dimana saat ini penjara dianggap sudah tidak tepat dan aman bagi pecandu narkotika untuk menjalani penyembuhan. Penelitian ini mengkaji pendekatan ibadah yang digunakan pada proses rehabilitasi dan dan penerapan perlindungan hukum bagi seseorang yang terlibat penyalahgunaan narkotika di Panti Rehabilitasi Baitu Syifa dalam perspektif Undang-Undang Narkotika Nomor 35 tahun 2009. Penelitian kualitatif ini menggunakan pendekatan perundang-undangan, kasus, dan konseptual. Hasil penelitian menemukan bahwa program rehabilitasi di Baitu Syifa tidak menyelisihi aturan yang terdapat pada pasal 57 UU. Nomor 35 Tahun 2009 yaitu yang menyatakan bahwa pemulihan residen  dapat diselenggarakan melalui pendekatan keagamaan. Pemulihan korban penyalahgunaan narkotika di Baitu Syifa berupa rutinitas kegiatan bernuansa Islami berdasarkan Al-Quran dan As-sunnah yang meliputi Treatment Community (TC) Islami,  Kajian Islam Ilmiah, amalan amalan sholeh seperti melakukan ibadah-ibadah wajib, ibadah-ibadah sunnah, pengobatan thibun Nabawi dan membaca Alquran. Pengembangan metode pendekatan ibadah di Panti Rehabilitasi Baitu Syifa telah disesuaikan dengan Hukum Islam